Private equity and venture capital in Europe : markets, techniques, and deals - Caselli, Stefano, 1969-; Negri, Giulia (Academic Press, 2021)
Private Equity and Venture Capital in Europe: Markets, Techniques, and Deals, Third Edition introduces private equity, investments and venture capital markets while also presenting new information surrounding the core of private equity, including secondary markets, private debt, PPP within private equity, crowdfunding, venture philanthropy, impact investing, and more. Every chapter has been updated with new data, cases, examples, sections and chapters that illuminate elements unique to the European model. With the help of new pedagogical materials, this updated edition provides marketable insights about valuation and deal-making not available elsewhere. As the private equity world continues to undergo many challenges and opportunities, this book presents both fundamentals and advanced topics that will help readers stay informed on market evolution. --